Modification of Polyethylene Glycol and Citric Acid on Palm Fiber Waste Nanofibers on the Adsorption of Violet Crystal Dyes - Lina Mahardiani; Nida Damayanti; Rizki Deva Maharani; Sulistyo Saputro; Endang Susilowati; Wirawan Ciptonugroho; Nanik Dwi Nurhayati (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
This study developed nanofibers derived from sugar palm fiber waste, incorporating citric acid and polyethylene glycol (PEG) modifications to adsorb crystal violet (CV) dye. The synthesis process involved alkalization-acid hydrolysis and bleaching techniques. Subsequent analyses of nanofiber characteristics were conducted using Fourier-Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). The efficacy of these modified nanofibers in adsorbing CV was quantitatively measured using an Ultraviolet-Visible (UV-Vis) spectrophotometer. The study successfully synthesized nanofibers from sugar palm fiber waste with modifications: PEG-modified nanofibers (NP 2 and NP 24) and citric acid-modified nanofibers (NS 2 and NS 24). These modifications resulted in nanofibers with a smooth, white texture. FTIR analysis of the samples (N, NP 2, NP 24, NS 2, and NS 24) revealed the presence of functional groups essential for cellulose, specifically -OH, C-H, and C-O groups. The addition of citric acid introduced a new group, C=O, albeit with very weak intensity. PEG modifications were evident from the stretching observed in the -OH groups. SEM analysis confirmed the presence of a layer on the nanofibers, attributed to citric acid (NS 2 and NS 24) and PEG (NP 2 and NP 24). XRD results indicated that the pre-and post-modification nanofibers exhibited a semi-crystalline phase. The adsorption mechanism was predominantly guided by Van der Waals electrostatic interactions between the absorbent material and the adsorbate. Intriguingly, the citric acid and PEG modifications did not significantly alter the adsorption outcomes. The adsorption capacity remained stable over time, as evidenced by measurements of 0, 15, 30, 45, 60, 90, and 120 minutes.